Penjor Bali and its Development - Putu Raka Setya Putra; Abay Delon Subarna (ARTic, 2021)
Streets in the province of Bali are very distinctive with penjor, especially on Balinese Hindu holidays such as Galungan and Kuningan. Penjor as part of a religious ceremony is full of meaning and the manufacture must be following the standard. Nowadays, penjor is used for events outside of the Balinese Hindu religion. Penjor has also changed its function as a decoration that adds to the lively area of Bali. To find out the development of penjor in Balinese society, a study was conducted with literature studies. The results show that based on its usefulness, penjor consists of two types, namely sacred penjor and decorative penjor. Penjor is used for other religious ceremonies such as Christmas, used for events such as New Year's, and other social occasions. Penjor forms are very diverse, with a variety of materials. The material and shape of the sacred penjor must follow the standard while the shape of the decorative penjor is free with more diverse materials. However, the essence of the meaning of penjor both for sacred penjor and decorative penjor does not shift, namely as a thanksgiving to God.